2016
DOI: 10.3390/ijerph13070708
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Neighborhood and Home Environmental Factors Associated with Television Viewing among Taiwanese Older Adults

Abstract: This study examined the associations between perceived neighborhood and home environmental factors and excessive television (TV) viewing time among Taiwanese older adults. The sample data was collected by administering computer-assisted telephone interviewers to 980 Taiwanese older adults (aged ≥ 65 years) living in two regions. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to examine the associations between self-reported perceived neighborhood and home environmental attributions and TV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…A similar association was found in Japanese adults when considering self‐reported transport‐related SB . Residential density was not associated with screen time …”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…A similar association was found in Japanese adults when considering self‐reported transport‐related SB . Residential density was not associated with screen time …”
Section: Resultssupporting
confidence: 78%
“…Destination measures were examined in five studies. The presence and density of and distance to destinations including recreational facilities, public parks, shops, entertainment facilities, food outlets, nonfood retail, health clinics, and civic services (eg, police station) were not associated with SB . However, the study by Barnett et al from Hong Kong revealed a significant positive relationship between the presence of places of worship (eg, churches, mosques) and nontransport sitting in older adults.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The potential ecological determinants of sedentary behaviour included aspects of the physical environment such as access to shops, pedestrian infrastructure, attractiveness of the neighbourhood [19,20,21,22], and self-reported measures of the presence of greenery or parks [19,22]. Aspects of social environment included area influences such as fear of crime [20,22], social cohesion or neighbourhood attachment [19,20], and individual specific interactions such as volunteering [19], participation in social or community groups or talking to neighbours [16,19,20].…”
Section: Introductionmentioning
confidence: 99%